2005
DOI: 10.1007/s10758-005-4579-3
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Activity in Computer-Supported Collaborative Problem Solving in Mathematics

Abstract: The purpose of this study was to analyse secondary school students' (N = 16) computer-supported collaborative mathematical problem solving. The problem addressed in the study was: What kinds of metacognitive processes appear during computersupported collaborative learning in mathematics? Another aim of the study was to consider the applicability of networked learning in mathematics. The network-based learning environment Knowledge Forum (KF) was used to support students' collaborative problem solving. The data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
1
4

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(34 citation statements)
references
References 17 publications
1
28
1
4
Order By: Relevance
“…Again, our findings do not support these concerns. Our results (similar to those of Hurme & Jarvela, 2005) indicated that the text-based nature of Knowledge Forum may in fact have benefited the students. Our analyses revealed that students made concerted efforts to communicate their ideas by developing a syncopated form of mathematical communication (Sfard, 1995) and naturally interwove words, numbers, and formal symbols in their interactions with each other.…”
Section: Research Questions Revisitedsupporting
confidence: 82%
“…Again, our findings do not support these concerns. Our results (similar to those of Hurme & Jarvela, 2005) indicated that the text-based nature of Knowledge Forum may in fact have benefited the students. Our analyses revealed that students made concerted efforts to communicate their ideas by developing a syncopated form of mathematical communication (Sfard, 1995) and naturally interwove words, numbers, and formal symbols in their interactions with each other.…”
Section: Research Questions Revisitedsupporting
confidence: 82%
“…There is also evidence that the use of metacognitive skills can help students to improve collaborative inquiry processes and domain understanding van Aalst and Chan 2007); and leads to high-quality learning and transfer (Didonato 2013;Vauras et al 2003). With appropriate scaffolding, students do engage in metacognitive processes as they work collaboratively on problems (Hurme and Järvelä 2005).…”
Section: Metacognitionmentioning
confidence: 99%
“…For instance, examples 1 and 6 are parts of a networked discussion in which the student pairs are intensively negotiating how to mark an angle of a polygon (see the discussions in Hurme & Jä rvelä , 2005). Example 7 shows that the students Bob and Michael are telling the other student pair that their note is a good one without saying why.…”
Section: A)mentioning
confidence: 99%